Coagulation Differences Detectable in Deep and Lobar Primary Intracerebral Hemorrhage Using Thromboelastography. Issue 5 (13th March 2020) - Roh, David; Torres, Glenda L; Cai, Chunyan; Zammit, Christopher; Reynolds, Alexandra S; Mitchell, Amanda; Connolly, E Sander; Claassen, Jan; Grotta, James C; Choi, Huimahn A; Chang, Tiffany R
Abstract: BACKGROUND: There are radiographic and clinical outcome differences between patients with deep and lobar intracerebral hemorrhage (ICH) locations. Pilot studies suggest that there may be functional coagulation differences between these locations detectable using whole blood coagulation testing. OBJECTIVE: To confirm the presence of interlocation functional coagulation differences using a larger cohort of deep and lobar ICH patients receiving whole blood coagulation testing: thromboelastography (TEG; Haemonetics). METHODS: Clinical and laboratory data were prospectively collected between 2009 and 2018 for primary ICH patients admitted to a tertiary referral medical center. Deep and lobar ICH patients receiving admission TEG were analyzed. Patients with preceding anticoagulant use and/or admission coagulopathy (using prothrombin time/partial thromboplastin time/platelet count) were excluded. Linear regression models assessed the association of ICH location (independent variable) with TEG and traditional plasma coagulation test results (dependent variable) after adjusting for baseline hematoma size, age, sex, and stroke severity. RESULTS: We identified 154 deep and 53 lobar ICH patients who received TEG. Deep ICH patients were younger and had smaller admission hematoma volumes (median: 16 vs 29 mL). Adjusted multivariable linear regression analysis revealed longer TEG R times (0.57 min; 95% CI: 0.02-1.11; P = .04), indicating longer clot formation times, in deep compared to lobar ICH. No other TEG parameter or plasma-based coagulation differences were seen. CONCLUSION: We identified longer clot formation times, suggesting relative coagulopathy in deep compared to lobar ICH confirming results from prior work. Further work is required to elucidate mechanisms for these differences and whether ICH location should be considered in future coagulopathy treatment paradigms for ICH.